COMPARATIVE STUDY OF PLASMA MEMBRANE INTEGRITY OF I SPERMATOZOA BY USING HOS MEDIUM AND DISTILLED WATER AND THEIR RELATION WITH POST THAW MOTILITY
This study was carried out on 148 frozen thawed semen, samples from cattle (58 from 11 HF bulls, 36 from 7 crossbred bulls, 33 from 6 Sahiwal bulls and 21 from 4 Jersey bulls